Adhesive and manufacturing method thereof, separator, electrode plate, electrode assembly, battery cell, battery, and power consuming device

By using adhesives of polyacrylate-based copolymers and lithium-content compounds in lithium-ion batteries, the problem of reduced efficiency of lithium-ion batteries during the initial charging and discharging process is solved, and the dual functions of lithium supplementation and adhesion are realized, and the circulation and amplification performance of the battery is improved.

JP2025507238AActive Publication Date: 2025-03-18CONTEMPORARY AMPEREX TECHNOLOGY (HONG KONG) LIMITED
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024520580
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-01-04
Filing Date
2023-06-05
Publication Date
2025-03-18
Estimated Expiration
2043-06-05

AI Technical Summary

Technical Problem

During the initial charging and discharging process of existing lithium-ion batteries, the efficiency of the SEI film formation and the side reaction of the positive electrode material will decrease, affecting the circulation and amplification performance.

Method used

An adhesive containing a polyacrylate-based copolymer and a lithium-content compound is used. By improving the water expansion and ionic conductivity of the polymer, the molecular weight and glass transition temperature of the polymer are controlled, thereby improving the adhesion performance of the adhesive, and having lithium supplement function, reducing dependence on independent lithium metal layers or lithium supplement layers.

Benefits of technology

Without adding an additional lithium supplement layer, this adhesive can quickly replenish lithium ions, improve ion transfer rate, enhance the structural stability of lithium ion batteries, improve dynamic performance, reduce electrochemical impedance, and improve cycling and amplification performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025507238000001_ABST
    Figure 2025507238000001_ABST
Patent Text Reader

Abstract

This application discloses an adhesive and its manufacturing method, a separator, an electrode plate, an electrode assembly, a battery cell, a battery, and a power consumption device, and relates to the field of battery technology. The adhesive includes a polyacrylate copolymer and a lithium-containing compound. The adhesive includes a polyacrylate copolymer and a lithium-containing compound, which allows the polymer to have very good swelling resistance, and exhibits good adhesion, improves ionic conductivity, and contributes to controlling the molecular weight and glass transition temperature of the polymer, thereby improving the adhesive performance. The adhesive further includes a lithium-containing compound, which allows the adhesive to have two functions of adhesive and lithium supplement at the same time, and eliminates the need to install an independent metallic lithium layer or lithium supplement layer in the lithium ion battery, and can improve the dynamic performance of the lithium ion battery, reduce the electrochemical impedance, and improve the cycle performance and power supply performance of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to the field of battery technology, and in particular to adhesives and their manufacturing methods, separators, plates, electrode assemblies, battery cells, batteries, and power consuming devices.

[0002] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to Chinese patent application No. 202310009976.4, proposed on January 4, 2023, for "Adhesive and Manufacturing Method Thereof, Separator, Electrode Plate, Electrode Assembly, Battery Cell, Battery, and Power Consumption Device," the entire contents of which are incorporated herein by reference. [Background technology]

[0003] Batteries are widely used in automotive power, power energy storage, portable electronic products, power tools, etc. During the initial charge and discharge process of the battery, problems such as the formation of SEI film on the surface of the negative electrode, the existence of some dead lithium and other foreign matter side reactions in the positive electrode material, etc., reduce the efficiency of the initial charge and discharge, and affect the cycle performance and power supply performance of the battery. Summary of the Invention

[0004] The present application has been made in view of the above problems, and aims to provide an adhesive having good adhesive performance, which further has a lithium replenishing effect, thereby contributing to reducing the electrochemical impedance, and can improve the cycle performance and rate performance of lithium ion batteries.

[0005] To achieve the above objective, the present application provides an adhesive and a manufacturing method thereof, a separator, a plate, an electrode assembly, a battery cell, a battery, and a power consuming device.

[0006] According to a first aspect, embodiments of the present application provide an adhesive, the adhesive including a polyacrylate-based copolymer and a lithium-containing compound.

[0007] Therefore, in the technical solution of the embodiment of the present application, the adhesive comprises a polyacrylate copolymer and a lithium-containing compound, which allows the polymer to have very good swelling resistance, and has a good adhesive effect, improves ionic conductivity, and contributes to controlling the molecular weight and glass transition temperature of the polymer, thereby improving the adhesive performance. In addition, the adhesive further comprises a lithium-containing compound, which allows the adhesive to have two functions of adhesive and lithium replenisher at the same time, which does not require the installation of an independent metallic lithium layer or lithium replenisher layer in the lithium ion battery, and can quickly replenish the lithium ions consumed in the lithium battery, increase the ion transmission rate, and improve the structural stability during the cycle of the lithium ion battery. When the adhesive is applied to the separator or plate and used in the lithium ion battery, it can improve the dynamic performance of the lithium ion battery, reduce the electrochemical impedance, and improve the cycle performance and the power supply performance of the lithium ion battery.

[0008] In any embodiment, the polyacrylate copolymer monomers include acrylate monomers, acrylonitrile monomers, and acrylamide monomers.

[0009] Thus, the acrylate monomer can improve the polymer swelling resistance and adjust the glass transition temperature of the polymer as a flexible monomer chain segment in the molecular chain segment, improving the toughness of the adhesive when applied and contributing to good adhesive action, the acrylonitrile monomer has a cyano group with strong polarity and contributes to improving ionic conductivity, and the acrylamide monomer plays the role of adjusting molecular weight. The above three monomers exist simultaneously and can control the molecular weight and glass transition temperature of the polymer, thereby improving the adhesive performance of the adhesive.

[0010] In any embodiment, the molar ratio of the acrylate monomer, the acrylonitrile monomer, and the acrylamide monomer is 1:(0.01-0.8):(0.01-0.15), and optionally 1:(0.05-0.7):(0.05-0.12). By controlling the molar ratio of the three monomers within the above ranges, the molecular weight and glass transition temperature of the polymer are further controlled, thereby improving the adhesive performance of the adhesive.

[0011] In any one of the embodiments, the acrylate monomer is methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, The acrylonitrile-based monomer includes at least one of acrylonitrile and methacrylonitrile, and the acrylamide-based monomer includes at least one of acrylamide, N-methylolacrylamide and N-butoxymethacrylamide. Experiments have shown that the above-mentioned three monomers have good lithium replenishment and adhesion effects, and further improve the cycle performance and power supply performance of lithium ion batteries.

[0012] In any embodiment, the mass ratio of lithium to the polyacrylate copolymer is 1:(10-1000), optionally 1:(100-600), and the above blending ratio allows the adhesive to have excellent lithium supplementation and adhesive effects at the same time.

[0013] In any embodiment, the adhesive has a volume average particle diameter Dv50≦50 μm, and optionally Dv50 is 7 to 8 μm. In the above particle diameter range, the adhesive and lithium replenishment effects are good.

[0014] According to a second aspect, an embodiment of the present application provides a method for producing an adhesive, the method including the steps of: adding a monomer of a polyacrylate copolymer to a first emulsifier solution to obtain a preliminary emulsion; adding an initiator to the preliminary emulsion to react with the initiator to obtain a reaction liquid; adding a lithium-containing material to the reaction liquid, adjusting the pH value of the reaction liquid to 7-8, and filtering the reaction liquid to obtain the adhesive.

[0015] Emulsion polymerization has a fast polymerization rate, and is favorable for heat conduction and temperature control. After the reaction reaches a high conversion rate, the viscosity of the emulsion polymerization system is still very low, and the dispersion system is stable and easy to control, realizing continuous operation. In addition, the lithium-containing material is used as a pH value regulator, which on the one hand saves the pH value regulator, reduces the addition of chemicals, and reduces the probability of side reactions; on the other hand, it can increase the Li content of the adhesive, which can quickly replenish the lithium ions consumed in the lithium battery, increase the ion transmission rate, and improve the structural stability of the lithium ion battery during cycling. When this adhesive is coated on a separator and used on a lithium ion battery, it can improve the dynamic performance of the lithium ion battery, reduce the electrochemical impedance, and improve the cycle performance and power supply performance of the lithium ion battery.

[0016] In any of the embodiments, in the step of adding polyacrylate-based copolymer monomers to the first emulsifier solution to obtain a pre-emulsion, the polyacrylate-based copolymer monomers include acrylate-based monomers, acrylonitrile-based monomers and acrylamide-based monomers.

[0017] The acrylate monomer can improve the polymer swelling resistance and adjust the glass transition temperature of the polymer as a flexible monomer chain segment in the molecular chain segment, improving the toughness of the adhesive when applied and contributing to good adhesive action, the acrylonitrile monomer has a highly polar cyano group, contributing to improving ionic conductivity, and the acrylamide monomer plays the role of adjusting molecular weight. The above three monomers exist simultaneously and can control the molecular weight and glass transition temperature of the polymer, thereby improving the adhesive performance of the adhesive.

[0018] In any embodiment, the molar ratio of the acrylate monomer, the acrylonitrile monomer, and the acrylamide monomer is 1:(0.01-0.8):(0.01-0.15), and optionally 1:(0.05-0.7):(0.05-0.12). By controlling the molar ratio of the three monomers within the above ranges, the molecular weight and glass transition temperature of the polymer are further controlled, thereby improving the adhesive performance of the adhesive.

[0019] In any one of the embodiments, the acrylate monomer is methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, The acrylonitrile-based monomer includes at least one of acrylonitrile and methacrylonitrile, and the acrylamide-based monomer includes at least one of acrylamide, N-methylolacrylamide and N-butoxymethacrylamide. Experiments have shown that the above-mentioned three monomers have good lithium replenishment and adhesion effects, and further improve the cycle performance and power supply performance of lithium ion batteries.

[0020] In any embodiment, the mass ratio of lithium to the polyacrylate copolymer is 1:(10-1000), optionally 1:(100-600), and the above blending ratio allows the adhesive to have excellent lithium supplementation and adhesive effects at the same time.

[0021] In any one of the embodiments, the step of adding an initiator to the preliminary emulsion to react with the initiator to obtain a reaction liquid includes: The preliminary emulsion is added to a second emulsifier solution under heating and refluxing conditions, and an initiator is added to react with the second emulsifier solution to obtain a reaction liquid.

[0022] The first and second emulsifiers allow the reactants to mix more uniformly, react more thoroughly, and distribute the product more uniformly.

[0023] In any embodiment, the reaction temperature is 20 to 90° C., and the reaction time is 20 to 40 minutes. As is clear from experiments, the reaction is more sufficient with fewer side reactions at the above reaction temperature and time.

[0024] In any one of the embodiments, in the step of adding a lithium-containing material to the reaction solution, adjusting the pH value of the reaction solution to 7 to 8, and filtering the reaction solution to obtain the adhesive, The lithium-containing material includes at least one of lithium hydroxide, lithium oxide, lithium carbonate, and lithium element. The lithium-containing material is used as a pH value adjuster, which can save the pH value adjuster, reduce the addition of chemicals, and reduce the probability of side reactions; on the other hand, it can increase the Li content of the adhesive, quickly replenish the lithium ions consumed in the lithium battery, increase the ion transmission rate, and improve the structural stability of the lithium ion battery during cycling.

[0025] The mass ratio of lithium to the polyacrylate copolymer is 1:(10-1000), and optionally 1:(100-600), and this blending ratio provides better pH adjustment and lithium supplementation effects.

[0026] According to a third aspect, an embodiment of the present application provides a separator, the separator comprising an adhesive according to an embodiment of the first aspect of the present application or an adhesive produced by a method for producing an adhesive according to an embodiment of the second aspect of the present application.

[0027] According to a fourth aspect, an embodiment of the present application provides a plate, the plate comprising an adhesive according to an embodiment of the first aspect of the present application or an adhesive produced by a method for producing an adhesive according to an embodiment of the second aspect of the present application.

[0028] According to a fifth aspect, an embodiment of the present application provides an electrode assembly, the electrode assembly including at least one of an adhesive according to an embodiment of the first aspect of the present application, an adhesive manufactured by the manufacturing method for an adhesive according to an embodiment of the second aspect, a separator according to an embodiment of the third aspect, and an electrode plate according to an embodiment of the fourth aspect.

[0029] According to a sixth aspect, an embodiment of the present application provides a battery cell, the battery cell including an electrode assembly according to the embodiment of the fifth aspect of the present application.

[0030] According to a seventh aspect, an embodiment of the present application provides a battery, the battery including a battery cell according to an embodiment of the sixth aspect of the present application.

[0031] According to an eighth aspect, an embodiment of the present application provides a power consuming device, the power consuming device comprising a battery cell according to an embodiment of the sixth aspect of the present application or a battery according to an embodiment of the seventh aspect. [Brief description of the drawings]

[0032] In order to more clearly explain the technical solutions in the embodiments of the present invention or the prior art, the following briefly introduces drawings that need to be used in the embodiments or prior art description. It is obvious that the drawings in the following description are only some embodiments of the present invention, and those skilled in the art can also obtain other related drawings based on these drawings without exerting creative efforts. [Figure 1] FIG. 1 is a schematic diagram of a battery cell according to one embodiment of the present application. [Diagram 2] FIG. 2 is an exploded view of the battery cell according to the embodiment of the present application shown in FIG. [Diagram 3] 1 is a schematic diagram of a battery module according to an embodiment of the present application; [Figure 4] 1 is a schematic diagram of a battery pack according to an embodiment of the present application; [Diagram 5] FIG. 5 is an exploded view of the battery pack according to the embodiment of the present application shown in FIG. 4. [Figure 6]1 is a schematic diagram of a power consumption device powered by a secondary battery according to an embodiment of the present application; [Figure 7] 1 is a SEM diagram of the adhesive of Example 1 of the present application. The realization of the object, the functional features and advantages of the present invention will be further explained with reference to the drawings in conjunction with the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0033] Hereinafter, with appropriate reference to the drawings, embodiments specifically disclosing the adhesive, separator, electrode plate, electrode assembly, battery cell, battery, and power consumption device of the present application will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of well-known matters and duplicated description of structures that are actually the same may be omitted. This is to avoid the following description becoming unnecessarily long and to allow those skilled in the art to easily understand. Note that the drawings and the following description are provided to allow those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.

[0034] The "ranges" disclosed in this application are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such defined ranges may be inclusive or exclusive of the extreme values, and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also envisaged. However, if 1 and 2 are listed as minimum range values, and 3, 4, and 5 are listed as maximum range values, the ranges 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are all envisaged. In this application, unless otherwise specified, the numerical range "ab" represents a shorthand representation of any combination of real numbers from a to b, where a and b are both real numbers. For example, the numerical range "0-5" represents a list of all real numbers between "0-5" already listed in this specification, and "0-5" is merely a shorthand for combinations of these numbers. Also, expressing a parameter as an integer ≧2 is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0035] Unless otherwise stated, all the embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0036] Unless otherwise stated, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0037] Unless otherwise stated, all steps in this application may be performed in sequence or randomly, and preferably in sequence. For example, the method includes steps (a) and (b) to mean that the method may include steps (a) and (b) performed in sequence, or may include steps (b) and (a) performed in sequence. For example, the method mentioned above may further include step (c) to mean that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), may include steps (a), (c) and (b), may include steps (c), (a) and (b), etc.

[0038] Unless otherwise specified, the terms "comprise" and "comprises" referred to in this application may be open ended or closed ended. For example, the terms "comprise" and "comprises" may further include or include other ingredients not listed, or may include or include only the ingredients listed.

[0039] Unless otherwise stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, "A or B" is satisfied if A is true (or exists) and B is false (or does not exist), if A is false (or does not exist) but B is true (or exists), or if both A and B are true (or exist).

[0040] Lithium ion batteries are widely used in automobile power, power energy storage, portable electronic products, power tools and other aspects. In the initial charge and discharge process of lithium ion batteries, due to problems such as the formation of an SEI film on the surface of the negative electrode, the existence of some dead lithium of the positive electrode material and other foreign side reactions, the efficiency of the initial charge and discharge is reduced. Lithium is replenished on the separator, and the main method is to pre-prepare a lithium layer separator, the lithium replenished separator includes a plurality of separator layers stacked on top of each other, the separator layer is a polymer film, a metallic lithium layer and a protective layer, the lithium-coated separator is to coat one side of the base film with a liquid adhesive, coat the other side surface with a lithium replenishment slurry, and obtain a lithium replenishment composite separator after drying in an oven, and the ceramic composite separator is provided with a ceramic layer and a ceramic-lithium replenishment layer on both sides of the base film, respectively, which can timely replenish consumed lithium ions, increase the ion transmission rate and improve the structural stability during the cycle of the lithium battery. These methods all have an independent metallic lithium layer or a lithium supplementary layer, which can improve the kinetics, but they affect the adhesion between the separator and the electrode plate, which affects the cycle performance and rate performance of the battery.

[0041] In other words, the inventors discovered that in actual operation, the lithium replenisher for batteries used in conventional technologies affects the adhesive strength between the separator and the electrode plates, and thus affects the cycle performance and rate performance of the battery.

[0042] Based on this, the applicant has examined a large amount of data and conducted a large amount of experiments and believes that if the two components, the lithium replenisher and the adhesive, can be combined into one material, there will be no need to add an extra lithium replenishment layer, thereby solving the problem of affecting the adhesive strength between the separator and the electrode plate, and thus affecting the cycle performance and rate performance of the battery.

[0043] Furthermore, the inventors have found after extensive experiments that the organic polymer obtained by polymerizing polymer monomers containing specific functional groups in a certain weight ratio has good adhesive properties and is suitable for fully exerting its adhesive properties under battery operating conditions, thereby contributing to improving the dynamic performance and safety performance of secondary batteries. Moreover, when the adhesive is used in a separator, it contributes to reducing the resistance of the separator and increasing the ionic conductivity of the separator, thereby improving the battery performance.

[0044] Considering the development of the market situation, the application of power batteries will be more and more widespread. Power batteries are not only used in energy storage power systems such as hydroelectric, thermal, wind and solar power stations, but also widely used in electric transportation tools such as electric bicycles, electric motorcycles, electric cars, and military equipment and aerospace. With the continuous expansion of the application fields of power batteries, the market demand is also continuously increasing.

[0045] Based on this, the present application provides adhesives, separators, plates, electrode assemblies, battery cells, batteries and power consuming devices.

[0046] According to a first aspect, embodiments of the present application provide an adhesive, the adhesive including a polyacrylate-based copolymer and a lithium-containing compound.

[0047] Polyacrylate copolymer is a general term for polymers produced through copolymerization reaction using acrylate as raw material. Acrylate has active double bonds and is easy to polymerize naturally and copolymerize. The copolymerization monomer may be one or more, and may be another acrylic acid compound or other unsaturated compound with double bonds, such as styrene, acrylonitrile, vinyl acetate, vinyl chloride, etc.

[0048] The lithium-containing compound is a compound that contains lithium, and may be either an organic substance or an inorganic substance. As long as it contains lithium element, any of them falls within the scope of protection of the present application.

[0049] Therefore, in the technical solution of the embodiment of the present application, the adhesive comprises a polyacrylate copolymer and a lithium-containing compound, which allows the polymer to have very good swelling resistance, and has a good adhesive effect, improves ionic conductivity, and contributes to controlling the molecular weight and glass transition temperature of the polymer, thereby improving the adhesive performance. In addition, the adhesive further comprises a lithium-containing compound, which allows the adhesive to have two functions of adhesive and lithium replenisher at the same time, which does not require the installation of an independent metallic lithium layer or lithium replenisher layer in the lithium ion battery, and can quickly replenish the lithium ions consumed in the lithium battery, increase the ion transmission rate, and improve the structural stability during the cycle of the lithium ion battery. When the adhesive is applied to the separator or plate and used in the lithium ion battery, it can improve the dynamic performance of the lithium ion battery, reduce the electrochemical impedance, and improve the cycle performance and the power supply performance of the lithium ion battery.

[0050] In any embodiment, the polyacrylate copolymer monomers include acrylate monomers, acrylonitrile monomers, and acrylamide monomers.

[0051] An acrylate monomer is a monomer containing an acrylate group, the structural formula of which is as follows: TIFF2025507238000002.tif30129 Here, R1 includes a hydrogen atom or an alkyl group of 1 to 6 carbon atoms, R2 includes a substituted or unsubstituted alkyl group of 1 to 15 carbon atoms, a cycloalkyl group of 3 to 6 carbon atoms, or an isobornyl group, and in the case of substitution, the substituent includes a hydroxyl group or an alkyl group of 1 to 6 carbon atoms.

[0052] The acrylonitrile monomer is a monomer containing an acrylonitrile group, and its structural formula is as follows: TIFF2025507238000003.tif30129 Here, R3 comprises a hydrogen atom or an alkyl group of 1 to 6 carbon atoms.

[0053] An acrylamide monomer is a monomer containing an acrylamide group, and its structural formula is as follows: TIFF2025507238000004.tif30129 Here, R4 includes a hydrogen atom or an alkyl group of 1 to 6 carbon atoms, and R5 includes a hydrogen atom, an alkyl group of 1 to 6 carbon atoms substituted with a hydroxyl group, or an alkoxy group of 1 to 6 carbon atoms.

[0054] Thus, the acrylate monomer can improve the polymer swelling resistance and adjust the glass transition temperature of the polymer as a flexible monomer chain segment in the molecular chain segment, improving the toughness of the adhesive when applied and contributing to good adhesive action, the acrylonitrile monomer has a cyano group with strong polarity and contributes to improving ionic conductivity, and the acrylamide monomer plays the role of adjusting molecular weight. The above three monomers exist simultaneously and can control the molecular weight and glass transition temperature of the polymer, thereby improving the adhesive performance of the adhesive.

[0055] As can be understood, the present application is not limited to the numbering method of each monomer in the polyacrylate copolymer, and the three monomers, acrylate monomer, acrylonitrile monomer and acrylamide monomer, may be arranged in order, or may be arranged randomly, and all of the above methods are within the scope of protection of the present application.

[0056] In any embodiment, the molar ratio of the acrylate monomer, the acrylonitrile monomer, and the acrylamide monomer is 1:(0.01-0.8):(0.01-0.15). For example, it may be any one of the following points or any two range values: 1:0.01:0.01, 1:0.01:0.15, 1:0.8:0.01, 1:0.8:0.15, 1:0.4:0.01, 1:0.4:0.15, 1:0.01:0.08, 1:0.8:0.08, but is not limited thereto. By controlling the molar ratio of the above three monomers within the above range, the molecular weight and glass transition temperature of the polymer are further controlled, thereby improving the adhesive performance of the adhesive.

[0057] In any one of the embodiments, the acrylate monomer is methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, The acrylonitrile-based monomer includes at least one of acrylonitrile and methacrylonitrile, and the acrylamide-based monomer includes at least one of acrylamide, N-methylolacrylamide and N-butoxymethacrylamide. Experiments have shown that the above-mentioned three monomers have good lithium replenishment and adhesion effects, and further improve the cycle performance and power supply performance of lithium ion batteries.

[0058] In any embodiment, the mass ratio of lithium to the polyacrylate copolymer is 1:(10 to 1000), and may be, for example, any one of 1:10, 1:100, 1:200, 1:300, 1:400, 1:500, 1:600, 1:700, 1:800, 1:900, 1:1000 or any range between two of them, but is not limited thereto. With the above blending ratio, the adhesive has excellent lithium supplementation and adhesive effects at the same time.

[0059] Lithium refers to lithium in a lithium-containing compound, and as can be understood, in the embodiments of the present application, lithium is connected to the polyacrylate copolymer by way of a polymeric ionic bond, and lithium is present in the adhesive in the form of a compound.

[0060] In any embodiment, the volume average particle diameter Dv50 of the adhesive is ≦50 μm, and in the embodiment of the present application, Dv50 is 7 to 8 μm. In the above particle diameter range, the adhesion and lithium replenishment effects are good.

[0061] In the embodiment of the present application, the particle size corresponding to when the cumulative particle size distribution percentage of the adhesive particles reaches 50% is Dv50, and the test method is as follows:

[0062] Refer to the standard GB / T 19077-2016 / ISO 13320:2009 Particle size distribution laser diffraction method. Use a laser granulometer (Malvern 3000, MasterSizer 3000) to test, and use a helium-neon red light source as the main light source. Take one clean small beaker, add 1g of the sample to be tested, add one drop of surfactant, add 20ml of deionized water (ensure the sample concentration is 8-12% light blocking), and sonicate at 53KHz / 120W for 5 minutes to ensure the sample is completely dispersed. Turn on the laser granulometer and test the background automatically after cleaning the light path system. Stir the already sonicated solution to be tested, disperse it evenly, and put it into the sample pool as required, and start to measure the particle size. The measurement result can be read from the instrument.

[0063] According to a second aspect, an embodiment of the present application provides a method for producing an adhesive, the method including the steps of: adding a monomer of a polyacrylate copolymer to a first emulsifier solution to obtain a preliminary emulsion; adding an initiator to the preliminary emulsion to react with the initiator to obtain a reaction liquid; adding a lithium-containing material to the reaction liquid, adjusting the pH value of the reaction liquid to 7-8, and filtering the reaction liquid to obtain the adhesive.

[0064] Emulsifiers are organic compounds that can form incompatible liquids into a stable emulsion. They are all surface-active substances that can reduce the interfacial tension between liquids, making it easier to emulsify incompatible liquids. During emulsification, the dispersed phase is uniformly distributed in the continuous phase in the form of very small liquid beads (with diameters between 0.1 microns and tens of microns), and the emulsifier forms a film or double electrical layer on the surface of these liquid beads to prevent them from coagulating with each other and maintain the stability of the emulsion. In the embodiment of this application, the emulsifier employed is sodium dodecyl sulfonate.

[0065] The pre-emulsion is a solution formed after emulsifying the monomers of the polyacrylate copolymer to form a stable emulsion of the monomers.

[0066] The initiator, also called radical initiator, refers to a compound that is easily decomposed into radicals (i.e. primary radicals) by heat, and can be used to initiate the radical polymerization and copolymerization reaction of ene and diene monomers, and can also be used in the crosslinking curing and polymer crosslinking reaction of unsaturated polyester. In the embodiment of the present application, the initiator employed is potassium persulfate.

[0067] The value of the hydrogen ion concentration index is generally called the "pH value." The value that indicates the degree of acidity or alkalinity of a solution is the negative value of the common logarithm of the hydrogen ion concentration contained. The pH value can be measured using pH test paper or a pH meter.

[0068] Emulsion polymerization has a fast polymerization rate, and is favorable for heat conduction and temperature control. After the reaction reaches a high conversion rate, the viscosity of the emulsion polymerization system is still very low, and the dispersion system is stable and easy to control, realizing continuous operation. In addition, the lithium-containing material is used as a pH value regulator, which on the one hand saves the pH value regulator, reduces the addition of chemicals, and reduces the probability of side reactions; on the other hand, it can increase the Li content of the adhesive, which can quickly replenish the lithium ions consumed in the lithium battery, increase the ion transmission rate, and improve the structural stability of the lithium ion battery during cycling. When this adhesive is coated on a separator and used on a lithium ion battery, it can improve the dynamic performance of the lithium ion battery, reduce the electrochemical impedance, and improve the cycle performance and power supply performance of the lithium ion battery.

[0069] As can be understood by those skilled in the art, in the above method of the specific embodiment, the order of making each step is not meant to be performed in strict order and constitutes any limitation on the implementation process, and the specific execution order of each step should be determined by its function and possible underlying logic.

[0070] In any of the embodiments, in the step of adding polyacrylate-based copolymer monomers to the first emulsifier solution to obtain a pre-emulsion, the polyacrylate-based copolymer monomers include acrylate-based monomers, acrylonitrile-based monomers and acrylamide-based monomers.

[0071] The acrylate monomer can improve the polymer swelling resistance and adjust the glass transition temperature of the polymer as a flexible monomer chain segment in the molecular chain segment, improving the toughness of the adhesive when applied and contributing to good adhesive action, the acrylonitrile monomer has a highly polar cyano group, contributing to improving ionic conductivity, and the acrylamide monomer plays the role of adjusting molecular weight. The above three monomers exist simultaneously and can control the molecular weight and glass transition temperature of the polymer, thereby improving the adhesive performance of the adhesive.

[0072] In any embodiment, the molar ratio of the acrylate-based monomer to the acrylonitrile-based monomer to the acrylamide-based monomer is 1:(0.01-0.8):(0.01-0.15).

[0073] The molar ratio of the monomers is the ratio of the mole numbers of the monomers, and may be, for example, any one of the following points or any two range values: 1:0.01:0.01, 1:0.01:0.15, 1:0.8:0.01, 1:0.8:0.15, 1:0.4:0.01, 1:0.4:0.15, 1:0.01:0.08, 1:0.8:0.08, but is not limited thereto. The molar ratio of the above three monomers is controlled within the above range, and the molecular weight and glass transition temperature of the polymer are further controlled, thereby improving the adhesive performance of the adhesive.

[0074] In any one of the embodiments, the acrylate monomer is methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, The acrylonitrile-based monomer includes at least one of acrylonitrile and methacrylonitrile, and the acrylamide-based monomer includes at least one of acrylamide, N-methylolacrylamide and N-butoxymethacrylamide. Experiments have shown that the above-mentioned three monomers have good lithium replenishment and adhesion effects, and further improve the cycle performance and power supply performance of lithium ion batteries.

[0075] In any embodiment, the mass ratio of lithium to the polyacrylate copolymer is 1:(10 to 1000), and may be, for example, any one of 1:10, 1:100, 1:200, 1:300, 1:400, 1:500, 1:600, 1:700, 1:800, 1:900, 1:1000 or any range between two of them, but is not limited thereto. With the above blending ratio, the adhesive has excellent lithium supplementation and adhesive effects at the same time.

[0076] In any one of the embodiments, the step of adding an initiator to the preliminary emulsion to react with the initiator to obtain a reaction liquid includes: The preliminary emulsion is added to a second emulsifier solution under heating and refluxing conditions, and an initiator is added to react with the second emulsifier solution to obtain a reaction liquid.

[0077] The first and second emulsifiers allow the reactants to mix more uniformly, react more thoroughly, and distribute the product more uniformly.

[0078] As can be understood, in the embodiments of the present application, the first emulsifier and the second emulsifier may be common emulsifiers in the art, such as sodium dodecyl sulfonate, and the present application is not limited thereto; furthermore, the first emulsifier and the second emulsifier may be the same or different, and the present application is also not limited thereto.

[0079] In any embodiment, the reaction temperature is 20 to 90°C, and may be, for example, any one of the points of 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, and 90°C, or a range value between any two of them, but is not limited thereto. The reaction time is 20 to 40 minutes, and may be, for example, any one of the points of 20 minutes, 22 minutes, 25 minutes, 28 minutes, 30 minutes, 33 minutes, 35 minutes, 37 minutes, and 40 minutes, or a range value between any two of them, but is not limited thereto. As is clear from experiments, the reaction is more sufficient and side reactions are less at the above reaction temperature and time.

[0080] As can be understood, the above reaction temperature and reaction time limitations may be satisfied either alone or simultaneously, and in the embodiments of the present application, both are satisfied simultaneously to make the reaction more complete and the side reactions less.

[0081] In any one of the embodiments, in the step of adding a lithium-containing material to the reaction solution, adjusting the pH value of the reaction solution to 7 to 8, and filtering the reaction solution to obtain the adhesive, The lithium-containing material includes at least one of lithium hydroxide, lithium oxide, lithium carbonate, and lithium element. The lithium-containing material is alkaline and can adjust the pH value of the reaction solution. The lithium-containing material is used as a pH value adjuster, which can save the pH value adjuster, reduce the addition of chemicals, and reduce the probability of side reactions. On the other hand, it can increase the Li content of the adhesive, quickly replenish the lithium ions consumed in the lithium battery, increase the ion transmission rate, and improve the structural stability of the lithium ion battery during cycling.

[0082] The mass ratio of lithium to the polyacrylate copolymer is 1:(10~1000), and may be, for example, any one of 1:10, 1:100, 1:200, 1:300, 1:400, 1:500, 1:600, 1:700, 1:800, 1:900, 1:1000 or any range between two of them, but is not limited thereto. The above blending ratio improves the pH value adjustment and lithium supplementation effect.

[0083] According to a third aspect, an embodiment of the present application provides a separator, the separator comprising an adhesive according to an embodiment of the first aspect of the present application or an adhesive produced by a method for producing an adhesive according to an embodiment of the second aspect of the present application.

[0084] When the adhesive of the first aspect of the present application is used in a separator, it contributes to reducing the resistance of the separator and increasing the ionic conductivity of the separator, thereby improving battery performance and effectively replenishing lithium.

[0085] The present application is not particularly limited to the type of separator substrate, and any known porous structure separator substrate having good chemical stability and mechanical stability can be selected.

[0086] In some embodiments, the separator substrate may be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a monolayer film or a multilayer composite film, without any particular limitation. When the separator is a multilayer composite film, the materials of each layer may be the same or different, without any particular limitation.

[0087] The separator of the present application can be manufactured by adopting a conventional method for separators in the art, for example, the adhesive described in the first embodiment of the present application can be dissolved in an organic solvent to obtain a slurry, and the slurry can be applied onto a separator material, and then the organic solvent can be removed by drying, that is, the separator of the present application can be obtained.

[0088] In some embodiments, the adhesive has a coating density on the separator substrate of 0.3-1.0 g / m 2 and 0.3-0.8 g / m 2 It is.

[0089] According to a fourth aspect, the present application provides an electrode plate, which comprises an adhesive produced by the adhesive manufacturing method described in the examples of the first aspect of the present application or the adhesive manufacturing method described in the examples of the second aspect of the present application. It comprises an adhesive produced by the adhesive manufacturing method described in the examples of the first aspect of the present application or the adhesive manufacturing method described in the examples of the second aspect of the present application. The electrode plate can be produced by a method commonly used in the art.

[0090] It should be explained that the electrode plate of the present application may be a positive electrode plate or a negative electrode plate.

[0091] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, the positive electrode film layer including the adhesive of the first aspect of the present application.

[0092] For example, a positive electrode current collector has two opposing surfaces in the thickness direction of the positive electrode current collector, and a positive electrode film layer is disposed on either one or both of the two opposing surfaces of the positive electrode current collector.

[0093] In some embodiments, the positive electrode current collector may be a metal foil sheet or a composite current collector. For example, an aluminum foil may be used as the metal foil sheet. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base layer. The composite current collector may be formed by forming a metal material (such as aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0094] In some embodiments, the positive electrode active material may be a positive electrode active material for batteries known in the art. For example, the positive electrode active material may include at least one of lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials for batteries may be used. These positive electrode active materials may be used alone or in combination of two or more. Here, examples of the lithium transition metal oxide include lithium cobalt oxide (e.g., LiCoO2), lithium nickel oxide (e.g., LiNiO2), lithium manganese oxide (e.g., LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM 333 (may be abbreviated as LiNi 0.5 Co 0.3 Mn 0.2 O2(NCM 523 (may be abbreviated as LiNi0.5 Co 0.25 Mn 0.25 O2(NCM 211 (may be abbreviated as LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM 622 (may be abbreviated as LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM 811 Lithium nickel cobalt aluminum oxide (e.g., LiNi 0.85 Co 0.15 Al 0.05 Examples of the lithium-containing phosphate having an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (e.g., LiFePO4 (which may be abbreviated as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (e.g., LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, and a composite material of lithium manganese iron phosphate and carbon.

[0095] In some embodiments, the positive electrode plate can be manufactured in the following manner: The components for manufacturing the positive electrode plate, such as the positive electrode active material, the conductive agent, the adhesive described in the examples of the first aspect of the present application, and any other components are dispersed in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry, which is then coated on a positive electrode current collector, and the positive electrode plate is obtained after processes such as drying and cold pressing.

[0096] In some embodiments, the loading of the adhesive described in the examples of the first aspect of the present application in the positive electrode plate is 1-3%, calculated based on the total weight of the positive electrode membrane layer.

[0097] Similarly, the electrode plate of the present application may be a negative electrode plate, which includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, the negative electrode film layer including the adhesive according to the first aspect of the present application.

[0098] For example, the negative electrode current collector has two opposing surfaces in the thickness direction of the negative electrode current collector, and the negative electrode film layer is disposed on either one or both of the two opposing surfaces of the negative electrode current collector.

[0099] In some embodiments, the negative electrode current collector may be a metal foil sheet or a composite current collector. For example, the metal foil sheet may be a copper foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (such as copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0100] In some embodiments, the negative electrode active material may be a negative electrode active material for batteries known in the art. For example, the negative electrode active material may include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, a silicone-based material, a tin-based material, and lithium titanate. The silicone-based material may be selected from at least one of a silicone element, a silicone oxide, a silicone carbon composite, a silicone nitrogen composite, and a silicone alloy. The tin-based material may be selected from at least one of a tin element, a tin oxide, and a tin alloy. However, the present application is not limited to these materials, and other conventional materials that can be used as a battery negative electrode active material may be used. These negative electrode active materials may be used alone or in combination of two or more.

[0101] In some embodiments, the negative electrode film layer further optionally comprises a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0102] In some embodiments, the negative electrode membrane layer optionally further comprises other auxiliary agents, such as a thickening agent (eg, sodium carboxymethylcellulose (CMC-Na)).

[0103] In some embodiments, the negative electrode plate can be manufactured in the following manner: Components for manufacturing the negative electrode plate, such as the negative electrode active material, the conductive agent, the adhesive described in the examples of the first aspect of the present application, and any other components are dispersed in a solvent (e.g., deionized water) to form a negative electrode slurry, which is then coated on a negative electrode current collector, and the negative electrode plate is obtained after processes such as drying and cold pressing.

[0104] In some embodiments, the amount of the adhesive described in the examples of the first aspect of the present application in the negative plate is 1-3%, calculated based on the total weight of the negative membrane layer.

[0105] According to a fifth aspect, an embodiment of the present application provides an electrode assembly, which comprises at least one of the adhesive of the first aspect of the present application, the adhesive manufactured by the adhesive manufacturing method described in the second aspect of the present application, the separator of the third aspect of the present application, and the electrode plate of the fourth aspect of the present application. The electrode assembly proposed in the present application has all the beneficial effects of the adhesives described above and will not be further described here.

[0106] According to a sixth aspect, an embodiment of the present application provides a battery cell, the battery cell including an electrode assembly according to the embodiment of the fifth aspect of the present application.

[0107] Generally, a battery cell includes a positive electrode plate, a negative electrode plate, an electrolyte, and a separator. During charging and discharging of the battery, active ions shuttle between the positive electrode plate and the negative electrode plate to store and release ions. The electrolyte functions to conduct ions between the positive electrode plate and the negative electrode plate. The separator is installed between the positive electrode plate and the negative electrode plate, and mainly functions to prevent short circuit between the positive and negative electrodes and allows ions to pass through.

[0108] The battery cell can be manufactured by a method commonly used in the art. For example, a positive electrode plate, a negative electrode plate and a separator can be manufactured into an electrode assembly by a winding process or a lamination process, and an electrolyte is injected into the electrode assembly and sealed to manufacture the battery cell.

[0109] The electrolyte serves to conduct ions between the positive and negative electrodes. The present application is not specifically limited to the type of electrolyte, which can be selected according to need. For example, the electrolyte may be liquid, gel, or all solid.

[0110] In some embodiments, the electrolyte is an electrolytic solution, the electrolytic solution including an electrolyte salt and a solvent.

[0111] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonate), lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluoro(oxalato)borate, lithium bis(oxalato)borate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate.

[0112] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, ethyl methyl sulfone, and diethyl sulfone.

[0113] In some embodiments, the electrolyte solution may further include optional additives, for example, additives for forming a negative electrode film, additives for forming a positive electrode film, and additives for improving some performance of the battery, such as additives for improving the overcharge performance of the battery, additives for improving the high temperature or low temperature performance of the battery, etc.

[0114] In some embodiments, the positive plates, negative plates and separators can be fabricated into an electrode assembly by a winding process or a lamination process.

[0115] In some embodiments, the battery cell may include an exterior body that may be used to package the electrode assembly and electrolyte.

[0116] In some embodiments, the battery cell housing may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The battery cell housing may be a pouch, such as a bag-like pouch. The pouch may be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0117] The present application is not particularly limited to the shape of the battery cell, which may be cylindrical, rectangular, or any other shape. For example, FIG. 1 shows a battery cell 5 with a rectangular structure as an example.

[0118] In some embodiments, referring to FIG. 2, the exterior body may include a case 51 and a cover plate 53. Here, the case 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate surround and form a receiving cavity. The case 51 has an opening communicating with the receiving cavity, and the cover plate 53 can cover the opening to seal the receiving cavity. The positive electrode plate, the negative electrode plate and the separator can form an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is packaged in the receiving cavity. An electrolyte is infiltrated into the electrode assembly 52. ​​The number of electrode assemblies 52 included in the battery cell 5 may be one or more, and can be selected by those skilled in the art according to specific actual needs.

[0119] According to a seventh aspect, an embodiment of the present application provides a battery, which includes a battery cell according to the embodiment of the sixth aspect of the present application. The specific form of the battery may be a battery module and a battery pack, and the number of battery cells included in the battery module may be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module.

[0120] Fig. 3 shows an example of a battery module 4. Referring to Fig. 3, in the battery module 4, a plurality of battery cells 5 may be arranged in sequence along the longitudinal direction of the battery module 4. Of course, the battery cells 5 may be arranged in any other manner. Furthermore, the plurality of battery cells 5 may be fixed by fasteners.

[0121] In either embodiment, the battery module 4 may further include a housing having an accommodating space, and the multiple battery cells 5 are accommodated in the accommodating space.

[0122] In some embodiments, the battery modules may be further assembled into a battery pack, and the number of battery modules included in the battery pack may be one or more, and the specific number can be selected by one skilled in the art according to the application and capacity of the battery pack.

[0123] 4 and 5 show an example of a battery pack 1. Referring to FIG. 4 and FIG. 5, the battery pack 1 may include a battery box and a plurality of battery modules 4 installed in the battery box. The battery box includes an upper housing 2 and a lower housing 3, and the upper housing 2 may cover the lower housing 3 to form a sealed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0124] According to an eighth aspect, an embodiment of the present application provides a power consuming device, the power consuming device comprising a battery cell according to an embodiment of the sixth aspect of the present application or a battery according to an embodiment of the seventh aspect.

[0125] The battery cells and batteries may be used as a power source for the power consuming devices, or as an energy storage unit for the power consuming devices, which may include, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0126] The power consumption device can be a secondary battery, a battery module, or a battery pack depending on its usage demand.

[0127] 6 shows an example of a power consumption device, such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. A battery pack or a battery module can be employed to meet the demand for high power output and high energy density of the secondary battery of the power consumption device.

[0128] Another example of the device may be a mobile phone, a tablet computer, a notebook computer, etc. These devices are generally required to be thin, and may employ a secondary battery as a power source.

[0129] The technical solution of the present invention will be described in more detail below with reference to specific examples and drawings. It should be understood that the following examples are only for interpreting the present invention, and are not intended to limit the present invention.

[0130] The relevant parameters of the adhesives of Examples 1 to 17 and Comparative Examples 1 and 2 are shown in Table 1 below.

[0131] TIFF2025507238000005.tif244170

[0132] Example 1 [Adhesive manufacturing] (1) Add 150g of deionized water and 3.6g of sodium dodecylsulfonate into a 500ml three-neck flask, emulsify with sufficient stirring for 15 minutes, and then add 75.24g of methyl acrylate, 18.55g of acrylonitrile, and 6.21g of acrylamide in that order, with a molar ratio of the three being 1:0.4:0.1. Stir for 60 minutes to obtain a preliminary emulsion of monomers, which is set aside as a reserve. (2) Add 100ml deionized water and 0.15g sodium dodecylbenzenesulfonate into a 500ml three-neck flask, heat to 80℃, emulsify for 15 minutes at a rotation speed of 2000r / min, and make the system fully emulsified. Then, slowly add the preliminary emulsion prepared in step (1) and the initiator solution (0.2g of potassium persulfate as initiator is dissolved in 30g of deionized water to form a solution). After the addition is completed, heat to 90℃ and keep it warm for 0.5h to react, and cool to 40℃. (3) After adjusting the pH value to 7 with LiOH aqueous solution, the stirring was stopped, filtered, and the material was discharged.

[0133] [Separator manufacturing] A commercially available PP-PE copolymer microporous film (manufactured by Zhuo Gao Electronics Technology Co., Ltd., model number 20 onwards) with a thickness of 20 μm and an average pore diameter of 80 nm was used as the substrate. The adhesive prepared above was stirred and mixed uniformly with deionized water to obtain a slurry (solid content is 20%). The slurry was uniformly coated on two surfaces of the substrate and dried to remove the solvent, and the coating density of the coating composition on the substrate was 1.0 g / m 2 Thus, a separator was obtained.

[0134] [Manufacturing of positive electrode plates] Polyvinylidene fluoride (PVDF), lithium iron phosphate (LFP), carbon black as a conductive agent, and N-methylpyrrolidone (NMP) were mixed homogeneously in a mass ratio of 1.2:58.38:0.42:40, and then prepared into a positive electrode slurry. 2 The aluminum foil positive electrode current collector was uniformly coated with the coating material in an amount of 0.1 to 1000g, and then dried, cold pressed, and slit to obtain a positive electrode plate.

[0135] [Manufacturing of negative electrode plates] Artificial graphite, acetylene black as a conductive agent, styrene butadiene rubber (SBR) as an adhesive, and sodium carboxymethylcellulose (CMC-Na) as a thickener were added to deionized water in a mass ratio of 96.2:1.0:1.6:1.2, thoroughly stirred to mix uniformly, and then prepared into anode slurry (solid content is 63%). This anode slurry was prepared at 98 g / m 2 The resultant mixture was then dried, cold pressed, and slit to obtain a negative electrode plate.

[0136] [Electrolyte production] At 25°C, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed according to a volume ratio of 1:1:1 to obtain a mixed solvent, and LiPF6 was dissolved in the mixed solvent to obtain an electrolyte, in which the concentration of LiPF6 was 1 mol / L.

[0137] [Secondary battery manufacturing] The positive electrode plate, separator, and negative electrode plate are stacked and wound in this order, and pre-pressurized (during this period, the separator is bonded to the electrode plate) to obtain an electrode assembly. The electrode assembly is placed inside an outer casing, and the above-prepared electrolyte is added. After going through processes such as packaging, standing, chemical conversion, and etching, a secondary battery is obtained.

[0138] The adhesives and separators, positive and negative electrode plates, electrolytes and secondary batteries of Examples 2 to 17 and Comparative Examples 1 and 2 are the same as those of Example 1, with the difference being that they are manufactured according to the parameters in Table 1.

[0139] The adhesive of Comparative Example 1 had no lithium, and the adhesive particle size of Comparative Example 2 was greater than 50 μm.

[0140] A scanning electron microscope image of the adhesive obtained in Example 1 was obtained as shown in FIG. 7. As can be seen, the adhesive produced in Example 1 of the present application has a spherical shape, with a particle size of about 8 μm.

[0141] The products of Examples 1 to 17 and Comparative Examples 1 and 2 were subjected to the following tests.

[0142] 1.Separator and electrode plate adhesion test: The battery plate and separator were stacked together and placed on a hot press machine, and the hot press parameters were set to 25°C temperature, 10t pressure, and 30s time to apply pressure to produce a bonded separator / positive plate sample, which was then cut into a 150 x 20mm rectangular bar. One side of the rectangular bar's plate was attached to a steel plate with double-sided tape, and the separator and plate were divided at one end of the rectangular bar into a length of 2cm along the longitudinal direction to produce a test sample.

[0143] The steel plate was held horizontally and fixed using the lower fixture of a universal testing machine (Xieqiang Instrument Manufacturing (Shanghai) Co., Ltd., model CTM2100), and the peeled end of the separator described above was fixed using the upper fixture of the universal testing machine and connected to a tensile machine. The test conditions were set to a tensile rate of 20 mm / min, and the sample was pulled horizontally for 10 cm. After the tensile force became stable, the tensile force value was recorded, and the adhesive strength between the separator and the electrode plate was obtained by the ratio of the tensile force value to the sample width.

[0144] 2. EIS data (electrochemical impedance spectrum): Using Shanghai Chenhua's CHI660D electrochemical station, a small amplitude sine wave voltage signal with a frequency of W1 is applied to the battery system, and the system responds by generating a sine wave current with a frequency of W2. The change in the ratio of the excitation voltage to the response current is the AC impedance test of the impedance spectrum of the electrochemical system. The test frequency range is 10mHz to 100kHz, and the amplitude is 5mV. Through the test, information such as the real part and imaginary part of the impedance can be obtained at different frequencies.

[0145] 3. Cycle performance of lithium-ion batteries: At 25°C, the battery produced in Example 1 was charged at a constant current of 1 / 3C to 3.8V, then charged at a constant voltage of 3.8V until the current became 0.05C, left to stand for 5 minutes, and then discharged at 1 / 3C to 2.0V, and the obtained discharge capacity was recorded as the initial capacity C0. The above steps were repeated for the same battery, and the discharge capacity Cn of the battery after the n-th cycle was recorded at the same time, and the battery capacity retention rate after each cycle Pn = (Cn / C0) x 100%. That is, the difference in cycle performance can be embodied by the battery capacity retention rate after 500 cycles.

[0146] 4.Lithium-ion battery multiplication performance: The test was performed using Wuhan Jinnuo Electronics' CT-2001 A LAND battery test system. The test environment was room temperature at 25°C, and the voltage range was 2.8 to 4.3V. Test batteries were assembled using electrode materials manufactured at the rates of 0.2C, 0.5C, 1C, 2C, 5C, and 0.2C (1C=200 mAh / g), and constant current charge / discharge cycles were performed five times. The battery capacity after the first five constant current charge / discharge cycles at 0.2C was recorded as C1, and the battery capacity after the second five constant current charge / discharge cycles at 0.2C was recorded as C2. The rate performance was expressed as P=(C2 / C1)×100%.

[0147] The test results are shown in Table 2 below.

[0148] TIFF2025507238000006.tif194165

[0149] As can be seen from Table 2, by comparing the comparative examples with the examples, it is clear that in Examples 1 to 25, the adhesive contains a polyacrylate copolymer, and the resulting adhesive has good adhesive performance, which is suitable for fully exerting its adhesive performance under battery operating conditions, and further contributes to improving the dynamic performance and safety performance of the battery, and further improves the battery cycle capacity retention rate.

[0150] In Comparative Example 1, there was no lithium in the adhesive, and in Comparative Example 2, the adhesive particle size was over 50 μm. As can be seen from Comparative Example 1, no lithium was added to the adhesive, and the adhesive adhesion, battery impedance, cycle performance and magnification performance were all relatively poor. As can be seen from Comparative Example 2, the adhesive particle size was too large, and the adhesive cycle performance and magnification performance were all relatively poor. The particle size was too large, which caused a reduction in adhesion, thereby affecting the cycle and magnification performance.

[0151] To sum up, the adhesive proposed in this application includes a polyacrylate copolymer and a lithium-containing compound, which allows the polymer to have very good swelling resistance, and also has a good adhesive effect, improves ionic conductivity, and contributes to controlling the molecular weight and glass transition temperature of the polymer, thereby improving the adhesive performance. In addition, the adhesive further includes a lithium-containing compound, which allows the adhesive to have two functions, namely, an adhesive and a lithium replenisher, and does not require an independent metallic lithium layer or lithium replenisher layer to be installed in the lithium ion battery, and can quickly replenish the lithium ions consumed in the lithium battery, increase the ion transmission rate, and improve the structural stability of the lithium ion battery during cycling. When the adhesive is applied to a separator or a plate and used in a lithium ion battery, it can improve the dynamic performance of the lithium ion battery, reduce the electrochemical impedance, and improve the cycle performance and the power supply performance of the lithium ion battery.

[0152] The above is merely a preferred embodiment of the present invention, and is not intended to limit the scope of the present invention, and those skilled in the art can make various modifications and variations to the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention should be included within the patent protection scope of the present invention. [Explanation of symbols]

[0153] 1 Battery pack 2 Upper case 3 Lower housing 4 Battery Module 5 Battery Cells 51 cases 52 Electrode Assembly 53 Cover plate

Claims

1. 1. An adhesive comprising a polyacrylate copolymer and a lithium-containing compound.

2. 2. The adhesive according to claim 1, wherein the monomers of the polyacrylate copolymer include an acrylate monomer, an acrylonitrile monomer, and an acrylamide monomer.

3. 3. The adhesive according to claim 2, wherein the molar ratio of the acrylate monomer to the acrylonitrile monomer to the acrylamide monomer is 1:(0.01-0.8):(0.01-0.15), and optionally 1:(0.05-0.7):(0.05-0.12).

4. The acrylate monomer includes at least one of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate, and / or The acrylonitrile-based monomer includes at least one of acrylonitrile and methacrylonitrile, and / or 4. The adhesive according to claim 2, wherein the acrylamide monomer includes at least one of acrylamide, N-methylolacrylamide, and N-butoxymethacrylamide.

5. The adhesive according to claim 1, characterized in that in the adhesive, the mass ratio of lithium to the polyacrylate-based copolymer is 1:(10-1000), optionally 1:(100-600).

6. 6. The adhesive according to claim 1, wherein the adhesive has a volume average particle size Dv50≦50 μm, and optionally 7 to 8 μm.

7. A method for producing an adhesive, comprising the steps of: adding monomers of a polyacrylate copolymer to a first emulsifier solution to obtain a pre-emulsion; adding an initiator to the preliminary emulsion to react with it to obtain a reaction liquid; adding a lithium-containing material to the reaction solution, adjusting the pH value of the reaction solution to 7 to 8, and filtering the reaction solution to obtain the adhesive.

8. 8. The method for producing an adhesive according to claim 7, wherein in the step of adding a polyacrylate-based copolymer monomer to the first emulsifier solution to obtain a preliminary emulsion, the polyacrylate-based copolymer monomer includes an acrylate-based monomer, an acrylonitrile-based monomer and an acrylamide-based monomer.

9. 9. The method for producing an adhesive according to claim 8, wherein a molar ratio of the acrylate monomer, the acrylonitrile monomer, and the acrylamide monomer is 1:(0.01-0.8):(0.01-0.15), and optionally 1:(0.05-0.7):(0.05-0.12).

10. The acrylate monomer includes at least one of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate, and / or The acrylonitrile-based monomer includes at least one of acrylonitrile and methacrylonitrile, and / or 10. The method for producing an adhesive according to claim 8, wherein the acrylamide monomer includes at least one of acrylamide, N-methylolacrylamide, and N-butoxymethacrylamide.

11. The step of adding an initiator to the preliminary emulsion to react with the initiator to obtain a reaction liquid includes:

8. The method for producing an adhesive according to claim 7, further comprising the steps of: adding the preliminary emulsion to a second emulsifier solution under heating and refluxing conditions; and adding an initiator to react with the second emulsifier solution to obtain a reaction solution.

12. The temperature of the reaction is between 20 and 90° C.; and / or The method for producing an adhesive according to any one of claims 7 to 11, wherein the reaction time is 20 to 40 minutes.

13. adding a lithium-containing material to the reaction solution, adjusting the pH value of the reaction solution to 7-8, and filtering the reaction solution to obtain the adhesive; The lithium-containing material includes at least one of lithium hydroxide, lithium oxide, lithium carbonate, and elemental lithium, and / or The method for producing an adhesive according to any one of claims 7 to 11, characterized in that the mass ratio of lithium to the polyacrylate-based copolymer is 1:(10-1000), and optionally 1:(100-600).

14. A separator, comprising an adhesive according to any one of claims 1 to 6 or an adhesive produced by the method for producing an adhesive according to any one of claims 7 to 13.

15. 14. An electrode plate, comprising an adhesive according to any one of claims 1 to 6 or an adhesive produced by the method for producing an adhesive according to any one of claims 7 to 13.

16. An electrode assembly, comprising at least one of the adhesive according to any one of claims 1 to 6, an adhesive manufactured by the method for manufacturing an adhesive according to any one of claims 7 to 13, a separator according to claim 14, and an electrode plate according to claim 15.

17. A battery cell comprising the electrode assembly according to claim 16.

18. A battery comprising the battery cell of claim 17.

19. 19. A power consuming device comprising a battery cell according to claim 17 or a battery according to claim 18.

Citation Information

Patent Citations

  • Preparation method of negative pole piece water-based binder

    CN111057184A

  • Preparation method of water-based lithium supplementing binder for lithium ion battery and preparation method of anode piece

    CN111253534A

  • Acrylonitrile copolymer binders and their applications in lithium-ion batteries

    JP2019526693A